'Rates of Exchange' Rather than Intellectual Exchanges: An Unknown Correspondence between Marcel Mauss and Victor Branford (1923–24) about the Franco-British Relationship in Interwar Sociology. Issue 1 (1st December 2020) - Rocquin, Baudry
Abstract: The newly found exchange of letters between Marcel Mauss and Victor Branford dated 1926 testifies to the active exchanges between both their traditions. Durkheimian sociology owed a great deal to the Branford-Geddes network of colleagues across the Channel, not less than a funding of the republication of their iconic journal, the Année sociologique . On the other hand, Branford was far from apologetic about his own tradition of thought and even went as far as to criticize the Institut Français de Sociologie in the 1920s. All this shows the enduring links between both countries in the field of sociology, contrary to what has often been held. Résumé: Un nouvel échange de lettres entre Marcel Mauss et le sociologue britannique Victor Branford daté de 1926 a été retrouvé. Il dépeint les relations actives qui existèrent entre deux traditions qu'on a souvent l'habitude d'opposer. Or, il faut noter que c'est grâce au financement par le réseau de Branford et Geddes que Mauss parvint à reprendre la publication de l' Année sociologique en France. De son côté, Branford ne se prive pas d'adresser quelques piques à ses collègues durkheimiens orthodoxes à l'Institut Français de Sociologie dans les années 20. Tout cela montre la force des liens qui unissent les deux pays en sociologie, contrairement à ce qu'on lit souvent.